2005
DOI: 10.1002/cncr.21228
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of lung carcinoma in Pennsylvania

Abstract: BACKGROUNDLung carcinoma remains the major cause of cancer death in North America and is even more common among military veterans. The objective of this study was to determine whether there were differences in the characteristics and survival of Pennsylvania patients with lung carcinoma in the Veterans Administration (VA) hospital system compared with patients in the rest of the state.METHODSThe Pennsylvania Cancer Registry was used to identify all patients who were diagnosed with lung carcinoma in the State o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Campling et al identified new LC patients diagnosed in 1995–1999 from the Pennsylvania Cancer Registry (n=28,798) to compare patient characteristics and survival among VA and civilian patients. 32 VA patients had worse overall survival, based on 5-year survival rate of 12% among VA patients and 15% among non-VA patients. When examined by race, this significant survival difference among VA and non-VA patients was observed in white patients but not blacks.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Campling et al identified new LC patients diagnosed in 1995–1999 from the Pennsylvania Cancer Registry (n=28,798) to compare patient characteristics and survival among VA and civilian patients. 32 VA patients had worse overall survival, based on 5-year survival rate of 12% among VA patients and 15% among non-VA patients. When examined by race, this significant survival difference among VA and non-VA patients was observed in white patients but not blacks.…”
Section: Resultsmentioning
confidence: 96%
“… 10 There were also conflicting findings in terms of survival benefit between patients treated in VA and non-VA systems. For example, one study 32 found that VA LC patients had worse overall survival than non-VA patients; however, two other studies found that VA LC patients had better all-cause 8 , 20 and cancer-specific survival. 8 Better overall survival was also found among VA CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 Among US military veterans, the 5-year survival is only 12%. 2 Early detection and surgical resection provide a curative option for patients with non-small cell lung cancer (NSCLC). However, once having undergone resection for early stage disease, there is very little data on long term post-operative mortality.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 Veterans treated at Veterans Affairs (VA) hospitals have a higher incidence of comorbidities, a greater frequency of multiple comorbid conditions, and an overall poorer level of health than non-veteran populations. 7,8 Together these factors suggest the importance of examining lung cancer survival among veterans.…”
Section: Introductionmentioning
confidence: 99%
“…Adjusted mortality was lower among Veterans who used VA care compared with male Medicare Advantage beneficiaries over 65 years of age (Selim, Berlowitz, et al, 2010;Selim, Kazis, Qian, et al, 2009;Selim et al, 2006;Selim et al, 2007). Mortality after some surgeries was higher among VA patients compared with non-Veterans receiving non-VA care (Campling et al, 2005;Chakkera et al, 2004;Glasgow et al, 2007;Henderson et al, 2007;Vaughan-Sarrazin, Wakefield, & Rosenthal, 2007) and after other surgeries, similar (Vaughan-Sarrazin, Wakefield, & Rosenthal, 2007). Mortality within one year of admission after hip fracture was 21 per cent lower among Veterans admitted to non-VA hospitals compared with Veterans admitted to VA hospitals (Richardson et al, 2013).…”
Section: Safety Of Care In Va Compared With Non-vamentioning
confidence: 93%